The pervasive and multifaceted influence of biocrusts on water in the world's drylands. (30th July 2020) - Eldridge, David J.; Reed, Sasha; Travers, Samantha K.; Bowker, Matthew A.; Maestre, Fernando T.; Ding, Jingyi; Havrilla, Caroline; Rodriguez‐Caballero, Emilio; Barger, Nichole; Weber, Bettina; Antoninka, Anita; Belnap, Jayne; et al.
Abstract: The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2, 997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier. Abstract : Summary diagram of the five moderators (biocrust type, climatic region [aridity zone], scale, soil texture, and disturbance) in relation to the seven hydrological attributes (time to ponding, time to runoff, sorptivity, infiltration, runoff, sediment production, soil moisture) across the full dataset. Purple and brown boxes denote significant ( p < .05) positive and negative effects, respectively, of biocrusts. Beige boxes denote insignificant effects, and grey boxes represent insufficient data to test possible effects. Biocrusts are widely distributed globally, and have marked effects on ecosystem properties and processes. A global assessment of biocrusts on hydrology revealed that they reduced the time for water to pond, on the surface, commence runoff, infiltrate and produce sediment, but increased soil moisture storage in the topsoil. Biocrust effects on hydrology varied markedly with soil texture, aridity, biocrust type, spatial scale, and level of disturbance. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands; information that is critical for sustainable management of Earth's dwindling dryland water supplies.